Job Satisfaction, Work Life Balance, and Trend Job Hopping on Gen Z - Iftikhar, Galih; Maskur, Adi; Prasetyo, Yanto; Sofiah, Diah (Jurnal Pengabdian Nusantara, 2025)
Job hopping is a phenomenon of frequent job changes that has become increasingly prevalent among Generation Z, who are young workers. Generation Z tends to switch jobs in order to meet their expectations related to satisfaction and work-life balance. This study aims to examine the relationship between job satisfaction and work-life balance with job hopping behavior among Generation Z. The subjects of this study were Generation Z employees currently working at PT. X Surabaya, with a population size of 130 individuals. The sampling technique used was probability sampling with the random sampling method, resulting in a sample of 108 respondents. Multiple regression analysis was employed as the data analysis technique. The results of the analysis show that job satisfaction and work-life balance have a simultaneous and significant relationship with job hopping. Both job satisfaction and work-life balance were found to have a negative association with job hopping, with job satisfaction having a stronger influence compared to work-life balance.